Costal Cartilage Assessment in Surgical Timing of Microtia Reconstruction. Issue 6 (September 2017) - Sun, Zhongyang; Yu, Xiaobo; Chen, Weiwei; Yang, Qinghua; Song, Yupeng; Zhou, Jiayu; Jiang, Haiyue
Abstract : Background: Rib cartilage growth is closely related to age and determines the feasibility and outcomes of auricular reconstruction. Ear reconstruction is performed as early as age 6 in efforts to treat children before school matriculation while allowing for sufficient rib growth. But there is controversy over the optimal timing of microtia reconstruction. This study employs CT imaging and surface scanning to guide the timing of auricular reconstruction in children. Methods: A retrospective analysis was performed on 6-year-old microtia patients between January 2016 and June 2016. A total of 37 patients were underwent preoperative 3D rib-cage CT measurements and normal auricle scanning measurement including: the length of 6th, 7th, and 8th costal cartilage, the width of 6th, and 7th costal cartilage, and the length of normal auricle. Then the data of costal cartilage were compared with the data of the auricle. Results: The average length of the 6th, 7th, and 8th rib cartilage on the right was 76.1 ± 9.2 mm (range, 61.1–94.9 mm), 102.6 ± 9.9 mm (range, 84.5–119.1 mm), and 75.4 ± 19.3 mm (range, 47.3–118.5 mm), respectively, and the the average helical length was 90.5 ± 6.8 mm (range, 76.9–101.5 mm). Comparing the above data, it was revealed that the age of 6 years was an optimal time for ear reconstruction with tissue-expanding technique. Conclusions: 3D rib-cage CT for preoperative measurement of costal cartilage could be a useful method for planning microtia reconstruction. According to our study, the amount of costal cartilage of almost all 6-year-old microtia patients is enough for ear reconstruction. So age 6 years is the optimal timing of auricular reconstruction with tissue-expanding method.